2021
DOI: 10.4300/jgme-d-20-00620.1
|View full text |Cite
|
Sign up to set email alerts
|

Blindfolding Improves Communication in Inexperienced Residents Undergoing ACLS Training

Abstract: Background Closed-loop communication (CLC) is associated with decreased medical errors and improved time-to-task completion during resuscitations. Depriving team leaders of sight during training may accelerate the acquisition of favorable communication skills; however, its effect on the frequency of CLC is unclear, especially with trainees. Objective We assessed the effect of depriving interns of sight during advanced cardiov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…Several studies found that adverse events decreased when team members used CLC, 14,16,17 whereas others reported that tasks were completed significantly faster with CLC, compared with nonstructured communication 12,16 . Most studies examining CLC were based on simulated emergencies 15,17–26 ; however, few have investigated the use of CLC in clinical practice 12,14,27 . The aim of this study was therefore to explore the use of CLC among anesthesia personnel in real-life interprofessional emergency teams.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found that adverse events decreased when team members used CLC, 14,16,17 whereas others reported that tasks were completed significantly faster with CLC, compared with nonstructured communication 12,16 . Most studies examining CLC were based on simulated emergencies 15,17–26 ; however, few have investigated the use of CLC in clinical practice 12,14,27 . The aim of this study was therefore to explore the use of CLC among anesthesia personnel in real-life interprofessional emergency teams.…”
Section: Introductionmentioning
confidence: 99%
“…Entre as modalidades utilizadas na simulação clínica, a técnica "olhos vendados" está sendo desenvolvida em diversos estudos internacionais, com a utilização de uma estrutura conceitual para organizar o gerenciamento de uma intervenção e pensamento crítico do aprendiz no papel de líder em cenários simulados de Reanimação Cardiorrespiratória (RCP), com ênfase na graduação médica (6,7,8) .…”
Section: Introductionunclassified
“…The modalities used in clinical simulation include the "blindfolded" technique, which is developed in several international studies, using a conceptual framework to organize the management of an intervention and critical thinking of the learner in the role of leader in simulated scenarios of Cardiopulmonary Resuscitation (CPR), with emphasis on medical graduation (6,7,8) .…”
Section: Introductionmentioning
confidence: 99%